GE_GERICHTE P/6468/2017 vom 21. Februar 2020 - GE Cour de justice (2020)
CONTRAINTE(DROIT PÉNAL);TENTATIVE(DROIT PÉNAL);PRINCIPE DE L'ACCUSATION;NOTIFICATION DE LA DÉCISION | CP.181; CPP.87; CPP.115.al1; CPP.9; CP.22.al1